The researcher participant relationship in educational research - Mitchell, Nick (2010)
This dissertation presents the outcomes of an empirical study of participation in educational research. Through individual interviews, the research explored the experiences and perceptions of a group of fifteen current or former teachers who had taken part in the educational research of others. This study suggests that the majority of this group of participants had been involved in research which did not conform to the expectations laid down in the ethical guidelines of the British Educational Research Association. Participants’ reported experiences, however, were not generally associated with concerns over research ethics but were often strongly influenced by the attitude of the individual researchers with whom they had contact. It also emerged that participants’ past histories of research involvement played a significant part in shaping their expectations and experiences of research involvement. This suggests that knowledge of the participation histories of those who take part in educational research might be a productive means for informing the development of research methodologies and could also suggest methods to target future recruitment of participants more effectively